Not entirely analog(ous): Low-power FM radio as community, relations and knowledge in context. (1st April 2020) - Dunbar-Hester, Christina
At the turn of the millennium, scholars and pundits reflected on how communication systems could shape events and societies, often while basking in the perceived glow of the then-novel Internet. Others pled for reasoned engagement with the interplay between communication infrastructures and the social life of knowledge, a much-needed corrective in a moment of rampant breathless digital utopianism. This article explores the interplay between communication infrastructures and the social life of knowledge through specific sociotechnical arrangements, low-power FM (LPFM) radio and large-scale commercial Internet-based 'platforms', both of which exist in our historical present. In particular, I use the formation of LPFM, which occurred at the same time that commercial Internet traffic picked up steam, in order to 'excavate the future': I return to a not-so-distant past to consider what might yet be. The article's central claim is that the case of LPFM is even more relevant now than at its inception, in a context where behemoth commercial Internet 'platforms' have come to dominate electronic communication.